2018
DOI: 10.1111/j.1936-704x.2018.03272.x
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on Water Resources among Anishinaabe and Non‐Native Residents of the Great Lakes Region

Abstract: Climate change and human population growth could reduce household water availability in the historically water‐rich Great Lakes region. It is critical to understand human‐water relationships in advance of policy actions that could result from reduced water supplies. Research on household water conservation typically occurs in a reactionary nature, in settings that are already water‐stressed. Furthermore, few studies involve Native American perspectives on this important topic. We used semi‐structured interview… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Perceptions are highly localized and individualistic, so these are contingent on our study area of the state of Michigan’s (USA) Lower Peninsula. Kozich et al (2018) found that around the Great Lakes region people bond strongly with water resources, however, that strong connection does not translate to motivation for water conservation likely because there is such an abundance of water resources in this region. In the U.S. (including our study area), there is no literature to date that addresses perceptions of forests and drinking water.…”
Section: Introductionmentioning
confidence: 99%
“…Perceptions are highly localized and individualistic, so these are contingent on our study area of the state of Michigan’s (USA) Lower Peninsula. Kozich et al (2018) found that around the Great Lakes region people bond strongly with water resources, however, that strong connection does not translate to motivation for water conservation likely because there is such an abundance of water resources in this region. In the U.S. (including our study area), there is no literature to date that addresses perceptions of forests and drinking water.…”
Section: Introductionmentioning
confidence: 99%
“…Several presenters highlighted the negative effects of mining and reclamation measures on tribal communities (Bulltail and Walter 2020) and water insecurity among tribes in the Southwest (Ellis and Perry 2020) and beyond. A few presenters included the social context in water research such as Kozich et al (2018). Presenters also demonstrated the success of hydrological research on tribal nations where university‐tribal partnerships were honored, nurtured, and strengthened through the project (Tsinnajinnie et al 2018; Tulley‐Cordova et al 2018).…”
mentioning
confidence: 99%